Perfume and cosmetic naming register as the reflection of social stratification - Nikiforova , Yevheniia; Havryliuk , Olha; Galitska, Elizaveta (Current issues of Ukrainian linguistics: theory and practice, 2021)
The article deals with the perfume and cosmetic naming register investigation in the aspect of its function as a source of lexical units used for further formation of naming units. The objects of this research are basic naming components that are distinguished within the structure of naming complexes represented in perfume and cosmetic goods. The naming integrated complex which represents the perfume and cosmetic name consists of four nominative components functioning in the mutual correlation. The initial position is connected with the A-brand component, the second position correlates with the B-basic component, the third one is the C-generic name component and the last is the D-functional-descriptive component. The leading position belongs to the B-component as a bearer of the basic name representing the corresponding item on the consumer goods market. The market segment correlates with consumers' social and economic status mutually. The market segment net functions as a factor indicating and underlying social stratification in the perfume and cosmetic naming space. The goods names that belong to the natural language according to the source of their origin are divided into two substantial groups (names of onym origin, names of appellative origin). The first group is formed involving transonymisation, the second one includes onymisation and is divided into various lexico-semantic groups. The involvement of anthroponym and toponym registers for creating perfume names is based on the basic knowledge of the recipients. The appellative naming register is an inexhaustible source for inventing perfume names. The differentiation of the naming register in its appellative part led to the separation of nine lexico-grammatic groups. Borrowings create the third source of perfume names. The fourth source of perfume and cosmetic names comprises artificially created words. If the perfume and cosmetic naming integrated complex consists of four components, the perfume and cosmetic naming register consists of four groups as well. These groups were distinguished according to the ways of name creation. The social stratification is reflected in the register in various ways. The first is an extralinguistic one according to three market segments. This way correlates with the A-brand component. The second is a linguistic way and correlates with the B-basic component. The linguistic way of social stratification is divided into explicit and implicit.
Keywords: anthroponym, appellative, artificially created word, borrowing, onym, onymisation, social stratification, transonymisation.